Pemanfaatan Sedimen Waduk Mrica Untuk Bahan Baku Bata Merah - Nastain Nastain; Paulus Setyo Nugroho (Jenderal Soedirman University, 2009)
Volume of water storage reservoir conditions Mrica from year to year decreases due to sedimentation. Efforts to reduce sediment in the reservoir has been done by way of flushing (flushing) periodically through the drawdown culvert (DDC), where the outcome is less effective and causes a lot of losses. This research was conducted in order to exploit the reservoir sediments Mrica for raw materials of red brick as an alternative effort to reduce sediment in the reservoir, as well as empowerment of communities around the reservoirs. Methods of research carried out by making a brick specimens made from sediments that were collected at the upstream, middle and downstream of the reservoir storage area. Laboratory tests conducted to determine the physical characteristics of sediment and the characteristics of the bricks produced. The results showed that: (1) Sediment basin headwaters Mrica coarse-textured sand with a sand content of 53%, the middle area is a sand-textured sand content of 62%, and the downstream region of 69% silt-textured with fine sand content of 31% , (2) Sediment that can be molded into bricks is a sedimentary rock containing 40% sand, with the color after the fire is reddish brown and smell of the less savory, (3) Depreciation is the largest dimension of the brick after the fire occurred on the bricks that were made of sediment downstream areas, ie an average of 21%, and (4) The compressive strength of bricks produced very little that is equal to 0.5% of the minimum standards required by the SNI 15-2094-2000.